1996
DOI: 10.1177/096032719601500304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicity induced by HT-2 toxin on human and rat granulo-monocytic progenitors with an in vitro model

Abstract: HT-2 toxin is a trichothecene mycotoxin occuring naturally in various agricultural products. Many in vitro studies have shown that HT-2 toxin is a major metabolite of the parent compound T-2 toxin. In man as well as in animals both toxins have been shown to cause alimentary intoxications and haematological disorders. Granulo- monocytic progenitors (CFU-GM) from human umbilical cord blood and from rat bone marrow were cultured in the presence of HT-2 toxin (10-7 M to 10-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The haematotoxicity of other trichothecene toxins (T-2 toxin and diacetoxyscirpenol) has been thoroughly investigated but DON has been less studied. Deoxynivalenol preferentially inhibits late-aggregate-forming cells, specifically colonyforming cells, in the rat, but being × 100 less toxic than T-2 (Lautraite et al 1997). According to Chowdhury et al (2005) 12 mg/kg DON in the feed was not haematotoxic and did not affect the ratio of peripheral blood leukocytes in laying hens.…”
Section: Discussionmentioning
confidence: 96%
“…The haematotoxicity of other trichothecene toxins (T-2 toxin and diacetoxyscirpenol) has been thoroughly investigated but DON has been less studied. Deoxynivalenol preferentially inhibits late-aggregate-forming cells, specifically colonyforming cells, in the rat, but being × 100 less toxic than T-2 (Lautraite et al 1997). According to Chowdhury et al (2005) 12 mg/kg DON in the feed was not haematotoxic and did not affect the ratio of peripheral blood leukocytes in laying hens.…”
Section: Discussionmentioning
confidence: 96%
“…In the experiments carried out by Abbas et al ( I 995) rat liver hepatoma cells were used and IC,,, of the mycotoxin fumonisin J3 was determined while Cawood et al (1994) used primary rat hepatocytes to test damage to the DNA caused by fumonisin B,. Lautraite et al (1995Lautraite et al ( , 1996 used cell lines of identical organ origin (granulo-monocytic progenitors) but from different origin (human and rat) to test toxicity of T-2 and HT-2 toxin.…”
Section: Resultsmentioning
confidence: 99%
“…Animal experiments reveal information on the overall toxicity of a mycotoxin and can point towards certain target organs. Toxicity of the mycotoxins may be tested in several cell lines derived from the target organs, both of human and animal origin, and results should be compared to determine relative sensitivities between species Lautraite et al 1995;Lautraite et al 1996). Cell lines have proven to be effective in research on mechanisms of toxicity (Riley et al 1994;Abbas el al.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] The presence of isolated cells in these treated cultures indicated that the total destruction of the cells did not occur. Yet, growth was not allowed.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] In this work, we study in vitro the effects of trichothecenes on erythroblastic progenitors using a culture model of human erythroblastic progenitors optimized for toxicological studies by Rio et all9 The four trichothecenes (T-2 and HT-2 toxins, DON and DAS) previously known to be very cytotoxic for human CFU-GM has been tested on human BFU-E . [15][16][17][18] Materials and methods Chemicals z Trichothecenes were purchased from Sigma (St Louis, USA). T-2 toxin (4/~, 15-diacetoxy-3a-hydroxy -8a -(3 -methylbutyryloxy) -12,13 -epoxytrichothec-9-ene), HT-2 toxin (15-acetoxy-3a, 4~3-dihydroxy -8a -(3 -methylbutyryloxy)-12,13-epoxytrichothec-9-ene) were produced from Fusarium sp.…”
mentioning
confidence: 99%